David Mitrany during the First World War. Some Ambiguities in His Biography - ALEXANDRESCU, Mihai (Studia Universitatis Babeș-Bolyai Historia, 2017)
In this paper, I will attempt to provide another overview of the David Mitrany activity in his first years in England (1908-1918), to emphasise the important role played by his Romanian origin on his work during the First World War, but also to fill in some gaps remained in his official biography for that period. In this respect, I opposed some information collected from David Mitrany personal collection to several details from the literature presenting him with a „diplomatic and intelligence work‟ in the wartime. These new data provide us another meaning for many of his works in the interwar period. Rezumat: David Mitrany în timpul Primului Război Mondial. Unele ambiguități din biografia sa. În acest articol, voi încerca să prezint o altă perspectivă asupra activității lui David Mitrany în primii săi ani din Anglia (1908-1918), să subliniez rolul important pe care l-a jucat originea sa românească asupra activității sale din Primul Război Mondial, dar și să completez unele omisiuni rămase în biografia sa oficială pentru acea perioadă. În acest sens, am opus unei informații provenite din arhiva personală a lui David Mitrany unor detalii din literatura care îl prezintă cu „activitate diplomatică și de intelligence” în anii războiului. Aceste noi date ne oferă un alt sens pentru multe dintre lucrările sale din perioada interblică. Cuvinte-cheie: David Mitrany, intelligence, diplomație, Legația României la Londra, Foreign Office.